2022
DOI: 10.1177/25151355221084535
|View full text |Cite
|
Sign up to set email alerts
|

Global herpes zoster incidence, burden of disease, and vaccine availability: a narrative review

Abstract: Herpes zoster (HZ) is a neurocutaneous disease that causes significant morbidity worldwide. The disease is caused by the reactivation of the varicella-zoster virus (VZV), which leads to the development of a painful, vesicular rash and can cause complications such as post-herpetic neuralgia and vision loss. Globally, the incidence of HZ is increasing, and it incurs billions in cost annually to the healthcare system and to society through loss of productivity. With the advent of effective vaccines such as the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 104 publications
0
46
0
1
Order By: Relevance
“…Regarding the economic analysis of vaccination, although there is signi cant heterogeneity, most studies determined that HZ vaccination was cost-effective when given at ages over 65 or 70 (33). In a study speci cally conducted in Spain, it was shown that the most cost-effective strategy in the general population was vaccination of the 65-year-old cohort and older with the recombinant vaccine (Shingrix) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the economic analysis of vaccination, although there is signi cant heterogeneity, most studies determined that HZ vaccination was cost-effective when given at ages over 65 or 70 (33). In a study speci cally conducted in Spain, it was shown that the most cost-effective strategy in the general population was vaccination of the 65-year-old cohort and older with the recombinant vaccine (Shingrix) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the FV-100 is a prodrug for the bicyclic nucleoside analog CF-1743 [ 43 ]. Previous RCT also indicated that FV-100 for the treatment of HZ could reduce the pain associated with HZ and the incidence of PHN [ 44 ]. Those drugs are very new, more research is needed to validate overall efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Herpes zoster results from reactivation of the varicella zoster virus (VZV) and has been increasing in recent years [ 1 ]. Reactivation occurs more than decades after the initial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Reactivation occurs more than decades after the initial infection. Suppressed immune responses due to such as aging and diabetes are considered to be the reason for reactivation of VZV [ 1 ]. Although it is found in various parts of the body with painful cutaneous vesicules, if it is found on the face, especially around the eyes, it is treated as herpes zoster ophthalmicus (HZO).…”
Section: Introductionmentioning
confidence: 99%